Implementation of Augmented Reality in Foreign Languages (English - Arabic) Using the Marker-Based Tracking Method - Banjarnahor, Joel Dakosta; Syahputri, Nita (Marqcha Institute, 2025)
Mastery of foreign languages, particularly English and Arabic, remains a challenge for Indonesian students due to limited exposure, low motivation, and the inadequacy of conventional learning media. This study aims to enhance students’ interest and learning outcomes in English and Arabic through the development and implementation of a Marker-Based Augmented Reality (AR) learning application. The research employs a design and development methodology, integrating AR with marker tracking using Vuforia and Unity, and evaluates the application across key functional scenes, including vocabulary recognition, interactive 3D object projection, quizzes, and learning materials. The results indicate that the AR application significantly improves engagement, motivation, and comprehension, allowing students to experience contextualized learning in an interactive and flexible environment. Marker-Based Tracking ensures accurate real-time projection of virtual objects onto physical markers, supporting multi-modal language acquisition, including vocabulary, pronunciation, and contextual understanding. Furthermore, the application demonstrates practical usability, scalability, and adaptability for self-directed and blended learning, highlighting its potential as a complementary educational tool. These findings suggest that AR can serve as an effective innovation to address low interest and achievement in foreign language learning, providing a model for immersive and interactive pedagogical practices. However, limitations such as device dependency and short-term evaluation underscore the need for further research to examine long-term learning outcomes, wider population applicability, and integration with markerless AR technologies. Overall, the study contributes to the emerging field of AR-mediated language learning by offering both theoretical insights and practical guidance for educators and developers.